Pelayanan Klaim Produk Jasa Asuransi PT. Asuransi Umum Bumiputera Muda 1967 - Miftahul Jannah; Fauzi Arif Lubis (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This research aims to understand how the service in Bumiputera Muda 1967 insurance company. This can be seen from the attitude and behavior of the worker figures concerned with the Bumiputera Muda 1967 insurance company itself. Insurance companies can be rated good in the eyes of customers through points including service. Service in an insurance company Insurance is one of the important instruments to protect the company. If the company is negligent in serving customers, it can be concluded that the company will be at financial risk in everyday life. However, services in insurance companies in each company can be different too. But the service in the Bumiputera Muda 1967 insurance company is very good. This can lead to a good bond between customers and workers at Bumiputera muda 1967 insurance company. This research was conducted using a qualitative approach, with the in-depth interview method as the main data collection tool. Research participants consisted of individuals from each customer of Bumiputera Muda 1967 insurance service users, who had used or considered insurance. Interview data was analyzed using thematic analysis method to identify the main themes that emerged.The results showed that the service at the Bumiputera Muda 1967 insurance company was very good. Not differentiating or grouping customers, both the service and each process is classified as very good and runs normally. These findings provide valuable insights in understanding how customers respond to services at Bumiputera muda 1967 insurance company. The implication of the results of this study is the importance of strategizing how to make customers happy and comfortable in the services of young bumiputra insurance companies.